Genome-Wide Detection of Copy Number Variations and Their Association With Distinct Phenotypes in the World’s Sheep - Salehian-Dehkordi, Hosein; Xu, Ya-Xi; Xu, Song-Song; Li, Xin; Luo, Ling-Yun; Liu, Ya-Jing; Wang, Dong-Feng; Cao, Yin-Hong; Shen, Min; Gao, Lei; Chen, Ze-Hui; Glessner, Joseph T.; et al. (Frontiers in Genetics, 2021)
Copy number variations (CNVs) are a major source of structural variation in mammalian genomes.Here we characterized the genome-wide CNV in 2,059 sheep from 67 populations all over the world using the Ovine Infinium HD (600K) SNP BeadChip. We tested their associations with distinct phenotypic traits by conducting multiple independent genome-wide tests. In total, we detected 7,547 unique CNVs and 18,152 CNV events in 1,217 non-redundant CNV regions (CNVRs), covering 245 Mb (~10%) of the whole sheep genome. We identified seven CNVRs with frequencies correlating to geographical origins and 107 CNVRs overlapping 53 known QTLs. Gene ontology and pathway enrichment analyses of CNV-overlapping genes revealed their common involvement in energy metabolism, endocrine regulation, nervous system development, cell proliferation, immune and reproduction. For the phenotypic traits, we detected significantly associated (adjusted P < 0.05) CNVRs harboring functional candidate genes, such as SBNO2 for polycerate, PPP1R11 and GABBR1 for tail weight, AKT1 for supernumerary nipple, CSRP1, WNT7B, HMX1 and FGFR3 for ear size, and NOS3 and FILIP1 in Wadi sheep, SNRPD3, KHDRBS2 and SDCCAG3 in Hu sheep, NOS3, BMP1 and SLC19A1 in Icelandic, CDK2 in Finnsheep, MICA in Romanov and REEP4 in Texel sheep for litter size. These CNVs and associated genes are important markers for molecular breeding of sheep and other livestock species.